A Prototype Of Role Based And Attribute Based De-duplication - Mishra, Dinesh; Patwa, Sanjeev (International Journal of Computer Sciences and Engineering, 2025)
Cloud storage services enable individuals and organizations to outsource data storage to remote servers. Cloud storage providers generally adopt data de-duplication, a technique for eliminating redundant data by keeping only a single copy of a file, thus saving a considerable amount of storage and bandwidth. However, an attacker can abuse de-duplication protocols to steal information. At present, there is a considerable increase in the amount of data stored in storage services, along with dramatic evolution of networking techniques. In storage services with huge data, the storage servers may want to reduce the volume of stored data, and the clients may want to monitor the integrity of their data with a low cost, since the cost of the functions related to data storage increase in proportion to the size of the data. To achieve these goals, secure de-duplication and integrity auditing delegation techniques have been studied, which can reduce the volume of data stored in storage by eliminating duplicated copies and permit clients to efficiently verify the integrity of stored files by delegating costly operations to a trusted party, respectively. This paper present study and development of a prototype for role and attribute based de- duplication